2022
DOI: 10.2340/17453674.2022.2753
|View full text |Cite
|
Sign up to set email alerts
|

How long does an elbow replacement last? A systematic review and meta-analysis of case-series and national registry reports with more than 10 years of follow-up

Abstract: Background and purpose: This study aims to determine, for the first time, generalizable data on the longevity and long-term function of elbow replacements.Methods: In this systematic review and meta-analysis, we searched MEDLINE and Embase for articles reporting 10-year or greater survival of total elbow replacements (TERs) and distal humeral hemiarthroplasty. Implant survival and patient reported outcome measures (PROMs) data were extracted. National joint replacement registries were also analyzed. We weighte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…With regard to elbow arthroplasty Evans et al 13 reported, in their systematic review and meta-analysis of case series and registry data, 92% 10-year survival for 628 linked total elbow replacements and 10-year PROMs from elbow replacements revealed a substantial improvement from baseline scores, again suggesting good longevity.…”
Section: Does Follow-up Beyond One Year Identify the Asymptomatic Fai...mentioning
confidence: 99%
“…With regard to elbow arthroplasty Evans et al 13 reported, in their systematic review and meta-analysis of case series and registry data, 92% 10-year survival for 628 linked total elbow replacements and 10-year PROMs from elbow replacements revealed a substantial improvement from baseline scores, again suggesting good longevity.…”
Section: Does Follow-up Beyond One Year Identify the Asymptomatic Fai...mentioning
confidence: 99%
“…The 25-year survivorship of total knee replacement from registries is 82% (Evans et al., 2019b). The reported 10-year survival rate for shoulder arthroplasty is 92% (Evans et al., 2020), for linked total elbow replacement 92% (Evans et al., 2022) and for ankle replacement 66% (Perry et al., 2022). In comparison, the highest reported survival rate for fourth-generation TWA at 15-year follow-up is 78% (Gil et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“… 1 However, despite technological advances, TEA continues to have higher failure rates than arthroplasty of the hip and knee. 2 - 5 …”
Section: Introductionmentioning
confidence: 99%